Updates in Hemodialysis - Suzuki, Hiromichi (IntechOpen, 2015)
In this special issue, reviews of various aspects of HD therapy were submitted from all over the world. In particular, reviews for recent advances in this area from leading experts have been contributed to the book Hemodialysis. In order to deliver optimal patient care, nephrologists need to understand and be highly knowledgeable in the mechanisms of multiple aspects of hemodialysis therapy. Moreover, this book will provide an important source of information for beginners and experts, basic scientists and physicians who want to have a true update on current clinical practice in hemodialysis.